Contemporary Outcomes of Combined Heart-Liver Transplant in Patients With Congenital Heart Disease. Issue 2 (February 2018) - Bryant, Roosevelt; Rizwan, Raheel; Zafar, Farhan; Shah, Shimul A.; Chin, Clifford; Tweddell, James S.; Morales, David L.
Abstract : Background: As more patients survive into adulthood with repaired congenital heart disease (CHD), transplant centers now have patients presenting with both end-stage cardiac and hepatic failure. An understanding of the contemporary outcomes with combined heart liver transplantation (CHLT) in patients with CHD is needed. Methods: A retrospective review of the outcomes of CHLT in CHD was conducted from October 1, 1987, to June 30, 2015, from the United Network of Organ Sharing (UNOS) database. Propensity score matched cohorts were formed for the assessment of posttransplant outcome: CHLT with CHD, CHLT without CHD, and isolated heart transplant for CHD (HT-CHD). Cohorts were matched based on age, body mass index, inotrope use, and ventilator support at the time of transplant. We assessed 30-day, 1-, 5-, and 10-year posttransplant survivals. Results: There were 61 437 heart transplants during the study period, of which 190 (0.3%) were CHLT. Among CHLT, 41(22%) patients had CHD. In 26 (63%) of these, the indication for CHLT was hepatic congestion/cirrhosis of cardiac origin. In the matched cohorts, the overall survival for CHLT with CHD at 30 days, 1, 5, and 10 years was 95%, 86%, 83%, and 83%, respectively; for CHLT without CHD, it was 100%, 92%, 92%, and 63%, respectively (vs CHLT with CHD: P = 0.49); and for HT-CHD, it was 90%, 84%, 63%, and 39% (vs CHLT with CHD: P = 0.03), respectively. Conclusions: The posttransplant outcome of CHLT, with and without CHD, is comparable. However, there is a trend toward better survival for CHLT for CHD compared with isolated heart transplant for CHD. Abstract : Using the United Network of Organ Sharing (UNOS) database, the authors report on the outcome of combined heart-liver transplantation (CHLT) in patients with congenital heart disease (CHD) who survive into adulthood, demonstrating comparable results to those obtained by patients undergoing CHLT for noncongenital heart diseases. Supplemental digital content is available in the text.